Niosome: A future of targeted drug delivery systems - Kazi Masud Karim; Asim Sattwa Mandal; Nikhil Biswas; Arijit Guha; Sugata Chatterjee; Mamata Behera; Ketousetuo Kuotsu (Wolters Kluwer Medknow Publications, 2010)
Over the past several years, treatment of infectious diseases and immunisation has undergone a revolutionary shift. With the advancement of biotechnology and genetic engineering, not only a large number of disease-specific biological have been developed, but also emphasis has been made to effectively deliver these biologicals. Niosomes are vesicles composed of non-ionic surfactants, which are biodegradable, relatively nontoxic, more stable and inexpensive, an alternative to liposomes. This article reviews the current deepening and widening of interest of niosomes in many scientific disciplines and, particularly its application in medicine. This article also presents an overview of the techniques of preparation of niosome, types of niosomes, characterisation and their applications.